Development of Novel EE/Alginate Polyelectrolyte Complex Nanoparticles for Lysozyme Delivery: Physicochemical Properties and In Vitro Safety - Sabrina Sepúlveda-Rivas; Hans F. Fritz; Camila Valenzuela; Carlos A. Santiviago; Javier O. Morales (MDPI AG, 2019)
The number of biologic drugs has increased in the pharmaceutical industry due to their high therapeutic efficacy and selectivity. As such, safe and biocompatible delivery systems to improve their stability and efficacy are needed. Here, we developed novel cationic polymethacrylate-alginate (EE-alginate) pNPs for the biologic drug model lysozyme (Lys). The impact of variables such as total charge and charge ratios over nanoparticle physicochemical properties as well as their influence over in vitro safety (viability/proliferation and cell morphology) on HeLa cells was investigated. Our results showed that electrostatic interactions between the EE-alginate and lysozyme led to the formation of EE/alginate Lys pNPs with reproducible size, high stability due to their controllable zeta potential, a high association efficiency, and an in vitro sustained Lys release. Selected formulations remained stable for up to one month and Fourier transform-Infrared (FT-IR) showed that the functional groups of different polymers remain identifiable in combined systems, suggesting that Lys secondary structure is retained after pNP synthesis. EE-alginate Lys pNPs at low concentrations are biocompatible, while at high concentrations, they show cytotoxic for HeLa cells, and this effect was found to be dose-dependent. This study highlights the potential of the EE-alginate, a novel polyelectrolyte complex nanoparticle, as an effective and viable nanocarrier for future drug delivery applications.